HUBUNGAN BRAND EXPERIENCE DAN BRAND LOVE TERHADAP BRAND LOYALTY: PERAN BRAND ATTITUDE SEBAGAI MEDIATOR - Cahyo, Septian Dwi; Patmasari, Eka Kurnia; Lestari, Ika Anggun (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
The company creates its competitive advantage through brand loyalty. Brand loyalty can be achieved when a company can offer a unique brand that  other brands do not. Brands must be well managed  to provide a competitive advantage. Building brand loyalty takes matching the character of a product with the consumer's personality so that the more positive is the consumer and the attitude towards the brand, the more attractive and reliable it isthe more positive  the consumer and attitude towards the brand. The purpose of this research  is to define the role of  brand attitude as a variable that mediates the relationship between brand experience and brand love and brand loyalty. This study focuses on consumers using local skin care brands in Indonesia. Local skin brands were chosen because the industry is currently  growing rapidly. The method used in this study is purposive sampling. of respondents who currently use local skin care brands. This study used  250 respondents from Indonesia. The results of this study show that mediating of role the brand attitude cannot mediate the relationship of brand experience and brand love with brand loyalty.